DOCK8 mutation diagnosed using whole-exome sequencing of the dried blood spot-derived DNA: a case report of an Iraqi girl diagnosed in Japan - Lika'a Fasih Y. Al-Kzayer; Hanadi Munaf H. Al-Aradi; Tomonari Shigemura; Kenji Sano; Miyuki Tanaka; Motoharu Hamada; Kenan Hussien Ali; Osamah Mohammed Aldaghir; Yozo Nakazawa; Yusuke Okuno (BMC, 2019)
Abstract Background Dedicator of cytokinesis 8 (DOCK8) deficiency (MIM #243700) is a rare disease, leads to a combined primary immunodeficiency (PID), and accounts for the autosomal recessive-hyper immunoglobulin E syndrome (AR-HIES). DOCK8 deficiency status characterizes by recurrent infections, atopy, and risk of cancer. Lymphoproliferative disease complicating PID, is difficult to diagnose. Our aim is to present a rare case of PID, and to the best of our knowledge, she is the first case of DOCK8 deficiency from Iraq. The genetic diagnosis was carried out in Japan using dried blood spot-based DNA transfer and whole-exome sequencing. Case presentation An 11-year-old Iraqi girl, of double first-cousin-parents, had a history of severe eczema, food allergy, and repeated infections. She presented with a jaw mass, bilateral cervical and axillary lymphadenopathy, and immunoglobulin (Ig) assays of 20, 3.3 and 1.7-fold above maximum normal level for age of IgE, IgA and IgG, respectively, along with a low IgM, eosinophilia and lymphopenia. Based on the jaw mass biopsy, non-Hodgkin lymphoma was suggested in Iraq, whereas histopathological re-evaluation in Japan revealed the diagnosis of a polyclonal reactive proliferation spectrum of lymphoproliferative disorders/plasmacytic hyperplasia, complicating PID. Whole-exome sequencing supported the diagnosis of PID by identifying a homozygous DOCK8 mutation with previously reported pathogenicity (NM_203447:c.3332delT, p.Phe1113Leufs*2), that may be attributed to consanguinity. Conclusions International collaboration using an effective DNA transportation technique and next-generation sequencing was the key to pinpoint the diagnosis of DOCK8 deficiency. Our case asserted that careful pathogenetic evaluation, in an advanced setting, was crucial for ruling out the neoplastic process. Pediatricians in areas with a high prevalence of consanguinity marriage should have a high index of suspicion of DOCK8 deficiency in patients with recalcitrant eczema, and frequent respiratory and skin infectious episodes.